2019
DOI: 10.12968/bjhc.2019.0017
|View full text |Cite
|
Sign up to set email alerts
|

Financial sustainability of NHS Foundation Trusts in England five years after the enactment of the Health and Social Care Act of 2012

Abstract: Background/Aims The enactment of the Health and Social Care Act (2012) led to significant structural changes in how hospital services are commissioned and has introduced direct competition with the private sector. The aim of this study was to assess the impact of the act on the financial position of the Shelford Group of NHS Trusts, 5 years after the act's enactment. Methods The levels of clinical activity, annual accounts and statements of financial position produced by the 10 Trusts for the financial years 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The National Audit Office Financial sustainability of the NHS reported that the cost remains the main issue in healthcare innovation. The NHS must cut costs to cover the anticipated £22 billion budget gap between patient demands and available resources [7,8]. Due to the recent innovations, there is also an increase in the percentage of older people, usually with much comorbidity, besides; the much-rising public expectations supposing that someone needs surgery or treatment for an illness or disease.…”
Section: Introductionmentioning
confidence: 99%
“…The National Audit Office Financial sustainability of the NHS reported that the cost remains the main issue in healthcare innovation. The NHS must cut costs to cover the anticipated £22 billion budget gap between patient demands and available resources [7,8]. Due to the recent innovations, there is also an increase in the percentage of older people, usually with much comorbidity, besides; the much-rising public expectations supposing that someone needs surgery or treatment for an illness or disease.…”
Section: Introductionmentioning
confidence: 99%